Epitope-based sieve analysis of Plasmodium falciparum sequences from a FMP2.1/AS02A vaccine trial is consistent with differential vaccine efficacy against immunologically relevant AMA1 variants. Issue 35 (31st July 2020) - Ouattara, Amed; Niangaly, Amadou; Adams, Matthew; Coulibaly, Drissa; Kone, Abdoulaye K.; Traore, Karim; Laurens, Matthew B.; Tolo, Youssouf; Kouriba, Bourema; Diallo, Dapa A.; Doumbo, Ogobara K.; Plowe, Christopher V.; et al.
Abstract: To prevent premature dismissal of promising vaccine programs, it is critical to determine if lack of efficacy in the field is due to allele specific-efficacy, rather than to the lack of immunogenicity of the candidate antigen. Here we use samples collected during a field trial of the AMA1-based FMP2.1/AS02A malaria vaccine, which incorporates the AMA1 variant encoded by the reference Plasmodium falciparum 3D7 strain, to assess the usefulness of epitope-based sieve analysis for the detection of vaccine-induced allele-specific immune responses. The samples used are from volunteers who received the malaria vaccine FMP2.1/AS02A or a control (rabies vaccine), during a vaccine efficacy field trial, and who later developed malaria. In a previous study, P. falciparum DNA was extracted from all samples, and the ama1 locus amplified and sequenced. Here, a sieve analysis was used to measure T and B-cell escape, and difference in 3D7-like epitopes in the two treatment arms. Overall, no difference was observed in mean amino acid distance to the 3D7 AMA1 variant between sequences from vaccinees and controls in B-cell epitopes. However, we found a significantly greater proportion of 3D7-like T-cell epitopes that map to the AMA1 cluster one loop (c1L) region in the control vs . the vaccinee group (p = 0.02), consistent with allele-specific vaccine efficacy. Interestingly, AMA1 epitopes in infections from vaccinees had higher mean IC50, and consequently lower binding affinity, than epitopes generated from the control group (p = 0.01), suggesting that vaccine-induced selection impacted the immunological profile of the strains that pass through the sieve imposed by the vaccine-induced protection. These findings are consistent with a vaccine-derived sieve effect on the c1L region of AMA1 and suggest that sieve analyses of malaria vaccine trial samples targeted to epitopes identified in silico can help identify protective malaria antigens that may be efficacious if combined in a multivalent vaccine.